The Perceptions of Young Adults Towards Social Gender Roles - Kaplan, Betul; Avcı, Sezer; Ortabağ, Tülay; Erkan, Doğan (European Journal of Therapeutics, 2023)
Objective: This study aims to provide an in-depth knowledge of the perspectives of young adults on gender roles. There is a lack of literature in the appropriate age classes. Methods: The study is descriptive in nature and includes 473 students. This research was conducted using a questionnaire and the Social Gender Perception Scale (SGPS) to collect data. Results: It was determined that 52.4% of the study participants were female and 47.6% were male. 63% of the participants were affiliated with the Faculty of Health Sciences, while the remainder were students from other faculties. The average SGPS score of the participants was 95.62±18.17, but this score varied based on socio-demographic variables. Specifically, being female, possessing an undergraduate degree or higher, studying in a health sciences faculty, and having a mother who completed primary school or higher were all linked to higher SGPS mean scores. Furthermore, statistical analysis revealed a significant difference between these groups (p<0.05). Conclusion: It is imperative that parents are provided with educational programs aimed at fostering knowledge of social gender roles and cultivating egalitarian attitudes and viewpoints. It is important to strategically design and execute research endeavours aimed at ascertaining the perspectives and attitudes of parents of young individuals with respect to societal gender roles.